History Of The Furniture Sector In Brazil (Journal of Namibian Studies : History Politics Culture, 2022)
This study explores the core realms of Entrepreneurship and Supply Chain in the context of the history of the furniture sector in Brazil. The research objective is to evaluate the correlation between trust management in entrepreneurs' profiles and the enhancement of relationship performance in supply chain management. Additionally, an analysis of the entrepreneur's endogenous and exogenous variables is conducted. The sample comprises emerging furniture companies in Minas Gerais, each with a tenure of five to ten years since establishment. Consequently, the study aims to address the following questions: How do enterprises identify potential actors within the sector's framework? What factors influence entrepreneurs' conduct in the supply chain? How can the nexus between trust management and relational variables be gauged to foster the success and maturity of nascent firms? How do the regulations in the state of Minas Gerais impact the emergence of new sustainable conceptual furniture ventures? Armed with answers to these and other questions, the intention is to construct and validate hypotheses derived from the theoretical model. The methodology employs both qualitative and quantitative techniques for comparative analysis and processing of empirical data. It endeavors to portray the entrepreneur's profile, behavior, and integration within the supply chain, all rooted in individual and interorganizational trust. The envisaged research outcomes possess the potential to enhance the prospects of the sampled companies and refine the comprehension of fundamental facets linked to the significance of supply chain management in furniture enterprises. This contribution encompasses models and concepts catering to the academic-scientific and business communities.